Exploring multilingual practices in billboard advertisements in a linguistic landscape - Anuarudin, Aini Andria Shirin; Chan, Swee Heng; Abdullah, Ain Nadzimah (Universiti Putra Malaysia Press, 2013)
Studying linguistic landscape (LL) is a relatively new area of sociolinguistics that encompasses written language on public road signs, billboard advertisements and shop fronts. The term, LL, can be traced to the seminal work of Landry and Bourhis (1997). It is through the lens of LL that this study aims to examine the linguistic practices and code choices in billboard advertisements in the ‘cityscape’ of a capital city. Spolsky (2004) states the real language policy of a community is likely to be found in its practices than in management of the policy. With this in mind, this study examines official documents that articulate and prescribe linguistic and code choice policies for billboard advertisements and apply the policies to analyse selected billboards along a stretch of highway in a cityscape. Thus, the reality of the practice is what matters most. The prescribed language policies provide a sense of the ideal that a society could strive for in nationhood practices; but the reality of practice reveals the choice and use. The results of these practices point to language accommodations made within a linguistically heterogeneous society. The LL is evidently a negotiation site of the reality and the ideal in language contact management affected by different forces that are politically and socially motivated.